A conserved GXXXG motif in the transmembrane domain of CLIC proteins is essential for their cholesterol-dependant membrane interaction - Hossain, Khondker Rufaka; Turkewitz, Daniel R.; Holt, Stephen A.; Herson, Leonie; Brown, Louise J.; Cornell, Bruce A.; Curmi, Paul M.G.; Valenzuela, Stella M. (Biochimica et biophysica acta. General subjects, 2019)
Sterols have been reported to modulate conformation and hence the function of several membrane proteins. One such group is the Chloride Intracellular Ion Channel (CLIC) family of proteins. The CLIC protein family consists of six evolutionarily conserved protein members in vertebrates. These proteins exist as both monomeric soluble proteins and as membrane bound proteins. To date, the structure of their membrane-bound form remains unknown. In addition to several studies indicating cellular redox environment and pH as facilitators of CLIC1 insertion into membranes, we have also demonstrated that the spontaneous membrane insertion of CLIC1 is regulated by membrane cholesterol. We have performed Langmuir-film, Impedance Spectroscopy and Molecular Docking Simulations to study the role of this GXXXG motif in CLIC1 interaction with cholesterol. Unlike CLIC1-wild-type protein, the G18A and G22A mutants, that form part of the GXXXG motif, showed much slower initial kinetics and lower ion channel activity compared to the native protein. This difference can be attributed to the significantly reduced membrane interaction and insertion rate of the mutant proteins and/or slower formation of the final membrane configuration of the mutant proteins once in the membrane. Conclusion: In this study, our findings uncover the identification of a GXXXG motif in CLIC1, which likely serves as the cholesterol-binding domain, that facilitates the protein's membrane interaction and insertion. Furthermore, we were able to postulate a model by which CLIC1 can autonomously insert into membranes to form functional ion channels. Members of the CLIC family of proteins demonstrate unusual structural and dual functional properties – as ion channels and enzymes. Elucidating how the CLIC proteins' interact with membranes, thus allowing them to switch between their soluble and membrane form, will provide key information as to a mechanism of moonlighting activity and a novel regulatory role for cholesterol in such a process. •A mechanism of CLIC1 interaction with membrane cholesterol is summarised.•A GXXXG motif in CLIC1 facilitates the protein's membrane interaction and insertion.•A model by which CLIC1 can autonomously insert into membranes to form functional ion channels has been postulated.